VET Policy Formation and Discourse in the EU : A mobile work force for a European labour market? - Cort, Pia [Verfasser] (My University, 2008)
"The Copenhagen process aims at a convergence if vocational education and training (VET) policies in Europe while at the same time respecting the diversity of national systems. The author sees this as a main tension within the process. Through a discursive reading of the process, an interpretation of it and its possible effects on VET discourse in Europe is offered. The interpretation points to the Copenhagen process as an intentional framing of VET, which, at Member State level, may lead to a narrowing national diversity as VET is subsumed under a common logic of creating a European labour market. The discursive reading is based on the 'what's the problem represented to be' approach developed by Carol Bacchi." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 2.1.1 Ökonomie / Märkte; G 1.2 Arbeitsmarkt; Berufsbildungssystem; EU-Bildungspolitik; Europäische Integration; EU-Binnenmarkt; Arbeitsmarkt